Penerapan Konseling Behavioral Menggunakan Teknik Kontrak Perilaku dalam Meningkatkan Kedisiplinan Belajar - Mega Aria Monica; Nova Erlina; Putri Reza Rahmaniar (Kuras Institute, 2022)
Learning discipline is something that must be considered in the learning process of students. Due to the Covid-19 pandemic, there has been a change in the learning system that started out conventionally (face-to-face) and has now changed to a distance learning system (online). In the implementation process, of course there are students who have not been able to adapt so that they experience a decrease in their learning discipline. The purpose of this study was to find out how the implementation of individual counseling services with the Behavior Contract technique in improving students' learning discipline. This research uses case study research with case study research design. The results showed that the implementation of individual counseling services using the behavior contract technique was carried out in several stages. With this behavior contact, it helps students make plans in making the right decisions so that they have a positive impact on students who can later change deviant behavior.